Avaliação da oralidade em sala de aula: um estudo envolvendo a progressão referencial no debate público regrado - Ross, Huanna Sperb (2018)
This master’s research was conducted in an eighth year Elementary School group in the municipal network of Itaara, Rio Grande do Sul, during August and December of 2017. Its primary objective is investigating the validity of an evaluation, which considers the argumentative oral performance of an eighth year student participating in a public ruled debate, which focuses the referential progression according to the theoretical focus. Our secondary objectives are the following ones: a) analyze if the lexical variation is developed in the introduction and the resuming of referents through the anaphores and cataphores. b) investigating if the activities that were evolved in the public debate can help students to develop improvements related to the construction of arguments; c) to find out if the rating criteria related to some aspects of different genders, as well as argumentation and referential progression helps the teacher and students to identify some frailties in the evaluations’ moment. In order to reach our objectives, our theoretical background is Text Linguistics, especially with Beaugrande e Dressler (1981), Bentes (2005), Fávero e Koch (2012), Koch (2014; 2015), Koch e Elias (2017) and the mediator conception of evaluation, which is studied by Romão (2005), Hoffmann (2008; 2014), Luckesi (2011). In reference to the text genders perspective, considering oral genders, we follow Dolz e Schneuwly (2004) and Marcuschi (2008). The methodological background comprises the action research, represented by Tripp (2005), Franco (2005) and Thiollent (2011); and the purpose of didactic sequence is according to Dolz, Noverraz e Schneuwly (2004). The advances or setbacks by the subject of this research (S22) were analyzed in the transcription of debates as well as the evaluation of the evaluation frame. In this frame, all criteria evolving text gender characteristics, argumentative aspects and referential progression were detailed. Considering the active subject of Text Linguistics and the teacher as the process mediator of teaching and learning, the evaluated practice was done by researcher and by S22, in order to find out the way that student analyzed and understood its improvement during the study. Thereby, we observed that S22 was gradually appropriating from the inherent text gender characteristics of the public ruled debate, and from the related aspects in the argumentation, mainly, in the utilization of arguments types according to the work of referential progression. According to this, we conclude that the education based in the perspective of mediator evaluation, based on the conceptions of Text Linguistics and Action Research, favor the improvement of S22’s oral text productions and for the adequacy of text gender approached.